Some New Results on Fixed Points for 𝜛-Distances in Complex-Valued Metric Spaces - Khuangsatung, Wongvisarut; Gebrie, Anteneh Getachew; Suanoom, Cholatis (Science & Technology Asia, 2024)
In this paper, we introduce the notion of a 𝜛-distance in complete complex-valued metric spaces and prove some fixed point theorems for mappings satisfying some appropriate inequalities in complete complex-valued metric spaces. Moreover, we deduce new fixed point results in complete complex-valued metric spaces and provide some examples to illustrate the usability of the obtained results.